BOOK CARRIER PETRAS MIKOLAINIS’ BOOK OF PROBLEMS IN ARITHMETIC - AŽUBALIS, ALGIRDAS (Knygotyra, 2015)
In the year 1909, P. Mikolainis (1868–1934) issued a mathematical book of problems for beginners in Tilsit. In the book, the knowledge of arithmetic bound with numbers from 1 to 100 was provided. By the way, the book was the first illustrated Lithuanian book of arithmetic problems. It was recommended to a teacher (in the case of using the book at school) to give supplemental tasks to getting-on pupils. Thus, the idea of individualization of teaching was emphasized. It was the second innovation offered in the book of problems, because no earlier published book of problems included such provisions. The third innovation was methodic instructions for teachers, provided in a smaller print. So, it was the first attempt to form Lithuanian didactics of mathematics. One more innovation was exercises (similar to today’s copybooks for practical tasks) where the pupils had to supplement the texts by inserting the necessary numbers, signs of operations, etc. Because P. Mikolainis had good skills in German and English, he used German and English books of problems of the time in developing his book of problems. It was an important innovation as well, because other authors usually used Russian coursebooks and books of problems as a base. Mathematical terms and names of numbers used in the book of problems by P. Mikolainis are similar to those used in other Lithuanian coursebooks and books of problems of that period.